Remarks on the Conceptualization of the Educational Problem in the Muslim World: The Case of Algeria - Nakib, Omar (Jurnal Usuluddin, 2020)
This study is a reflection into the methodological considerations that must be adopted to tackle the educational problem in the Arab and Muslim countries: the case of Algeria. The purpose is to discuss those methodological considerations that may pave the way to an objective approach of the educational problem in Algeria. This is to provide the researchers with some methodological tools to formulating the educational problem. An attempt has been made to address research questions, i.e. How should we conceptualize the educational problem in the Arab and Muslim countries: The case of Algeria? To conclude, this reflection requires us to give more importance to these methodological considerations to be able to state the educational problem in the Arab-Muslim lands in the appropriate manner. And, the elucidation of the concept of the ‘problem’ in educational research is an inevitable necessity. This is to pave the way for Muslim educational theorizers to grasp the essential components of the educational problem as a basic step to resolve it. The reason is that the educational problem is one of the important challenges facing the modern state and the epicentre of the current global civilizational conflict. The desired model of man, is the pivotal concern of philosophy of education. That is why, the educational problem in the Arab-Muslim lands is how to re-qualify the contemporary Muslim man to move from the state of being a backward man to the state of a civilized human being.